Population migration: implications for lymphatic filariasis elimination programmes. - K D Ramaiah (Public Library of Science (PLoS), 2013)
Human population migration is a common phenomenon in developing countries. Four categories of migration-endemic to nonendemic areas, rural to urban areas, non-MDA areas to areas that achieved lymphatic filariasis (LF) control/elimination, and across borders-are relevant to LF elimination efforts. In many situations, migrants from endemic areas may not be able to establish active transmission foci and cause infection in local people in known nonendemic areas or countries. Urban areas are at risk of a steady inflow of LF-infected people from rural areas, necessitating prolonged intervention measures or leading to a prolonged "residual microfilaraemia phase." Migration-facilitated reestablishment of transmission in areas that achieved significant control or elimination of LF appears to be difficult, but such risk can not be excluded, particularly in areas with efficient vector-parasite combination. Transborder migration poses significant problems in some countries. Listing of destinations, in endemic and nonendemic regions/countries, and formulation of guidelines for monitoring the settlements and the infection status of migrants can strengthen the LF elimination efforts.